2007
DOI: 10.1111/j.1600-0838.2007.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine status in former top‐level male athletes: possible effect of physical activity and physical fitness

Abstract: The importance of elevated homocysteine (Hcy) as a risk marker for cardiovascular disease is continuously under debate. Lifestyle factors may increase the total Hcy (tHcy) level of the plasma, but there are no consistent findings relating to Hcy, physical activity, and cardiorespiratory fitness. Cross-sectional measurement from an ongoing follow-up study was performed on 77 former male athletes and 33 sedentary controls (age range 35-62 years). Lifestyle parameters (current physical activity patterns, smoking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 32 publications
2
42
0
1
Order By: Relevance
“…Moreover, in an investigation conducted by Nygård et al [44], results showed that physical inactivity was associated to higher tHcy [44]. This author suggests that exercise exerts most favorable effects in subjects with hyperhomocysteinemia, as shown by Unt et al [34], who found higher tHcy concentrations in ex-athletes returning to a sedentary lifestyle comparing to those who continued being active [34]. In this study, vitamin status or dietary habits did not reveal any difference.…”
Section: Relation Of Physical Activity Levels And/ or Cardiorespiratosupporting
confidence: 49%
“…Moreover, in an investigation conducted by Nygård et al [44], results showed that physical inactivity was associated to higher tHcy [44]. This author suggests that exercise exerts most favorable effects in subjects with hyperhomocysteinemia, as shown by Unt et al [34], who found higher tHcy concentrations in ex-athletes returning to a sedentary lifestyle comparing to those who continued being active [34]. In this study, vitamin status or dietary habits did not reveal any difference.…”
Section: Relation Of Physical Activity Levels And/ or Cardiorespiratosupporting
confidence: 49%
“…Mainly, low folate and vitamin B12 levels impair the methylation that converts HCY into methionine. Although there is some evidence of beneWcial eVects of physical activity on reduction of plasma HCY concentrations, the results are not consistent throughout studies and the interpretation of pathways involved in exercise modulation of HCY is not conclusive (Herrmann et al 2003;Okura et al 2006;Unt et al 2007).…”
Section: Introductionmentioning
confidence: 70%
“…Some studies have directly compared the eVects of physical activity on plasma HCY concentrations, and these studies have been mostly limited to men or over 45-yearold women (Herrmann et al 2007;Mora et al 2006;Unt et al 2007;Zee et al 2007;Zinellu et al 2007). Few papers investigated factors modulating HCY concentrations in pre-menopausal women De Cree et al 1999;Randeva et al 2002), although knowledge of factors inXuencing HCY levels in young healthy females of reproductive age have potential implications for early prevention of venous thrombosis, CVD and adverse pregnancy outcomes (Refsum et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…If there was any doubt over whether the athletes were elite, the authors of the articles were emailed for further clarification; in total 14 authors were emailed. The methodology of the 59 elite athlete articles were then reviewed in detail (step 5), and 33 articles were excluded from the final review because of one or more of the following: the authors did not state the training status of the subjects, or respond to requests for subject details (n = 4) [38,46,73,74]; the subjects were masters/former athletes (n = 3) [75][76][77], amateur or college level athletes (n = 3) [ [78][79][80], athletes, but not elite status (n = 4) [42,48,81,82] or navy recruits (n = 1) [83]; participants were elite, but under 18 years of age (n = 2) [84,85]; only one sampling point was included, compared with healthy control data (n = 1) [86]; less than half of the study population were elite (n = 2) [87,88]; there were insufficient measures of redox balance [89,90] (n = 2); the training volume was not indicative of elite cyclists at 90 km per week (n = 1) [91]; the studies were RCTs involving antioxidant supplementation in elite athletes (n = 10) [92][93][94][95][96][97][98][99][100][101]. In addition, the methodological qualities of the articles were checked using methodological quality assessment criteria for the observational articles to be included in the final analysis (step 6).…”
Section: Study Selectionmentioning
confidence: 99%